Penggunaan Microsoft Excel untuk Meningkatkan Efektivitas Transaksi Keuangan pada Nota Penjualan dan Faktur Pajak di PT XYZ - Gilang Romadoni; Muhadjir Anwar (Nirta Learning Centre, 2026)
This study aims to analyze Microsoft Excel as an appropriate tool for improving work effectiveness, such as recording financial transactions, particularly sales receipts and tax invoices, at PT XYZ. The method used was a case study approach within the context of an internship, allowing the researcher to directly analyze work processes before and after using Excel. This included the use and utilization of formulas, dynamic tables, data validation, and automatic formatting. The results of the study have shown that implementing Excel in completing tasks, particularly sales receipts and invoices, helped the recapitulation process by minimizing errors by more than 50%. Furthermore, the author contributed to streamlining time and work methods, resulting in faster completion of work. Another impact of the implementation is faster staff working hours and interdepartmental communication, resulting in a lighter and easier workload. The use of technology and computerization in financial management and transaction systems not only streamlines work and makes completion easier, but also minimizes human error and obstacles that occur in manual processes. Supervision and security are improved without reducing the working hours of PT XYZ employees.